E.B. White : the emergence of an essayist - Root, Robert L. (University of Iowa Press, 1999)
"Robert Root explores the milieu in which White began writing the "Notes and Comments" section of the New Yorker and puts in perspective the influence of popular "colyumists" like Don Marquis and Christopher Morley on the tone and form of White's work as a "paragrapher." He examines White's persistent disaffection with the demands and limitations inherent in his "Comment" pieces for the New Yorker and his experiences as a columnist for Harper's Magazine, where his "One Man's Meat" feature produced his most enduring essay, "Once More to the Lake," and took the segmented column form to new levels of accomplishment. Drawing on White's manuscripts, Root's literary analysis of early drafts demonstrates how unique White's essays were."--Jacket